Almeno una stella. Un progetto di tutoraggio per gli adolescenti immigrati - Napoli, Monica (La melagrana - Open Access, 2016)
The project "Almeno una stella" ("At least one star") is a network of welcome and accompaniment for teen immigrants, which are supported by tutors (the "stars" of the title) chosen among university young students. Many tutors has foreign origin and a past of migration in common with the boys that accompany. The project was experienced in six different territories: Milan (lead city), Turin, Bologna, Arezzo, the province of Trento, Friuli. The text describes the project, its protagonists and its local variations.